2018
DOI: 10.1029/2017tc004636
|View full text |Cite
|
Sign up to set email alerts
|

Crustal Strain in the Marmara Pull‐Apart Region Associated With the Propagation Process of the North Anatolian Fault

Abstract: Key Points:• Structural map and geological cross-section of the Ganos-Gelibolu fold system in the Dardanelles region.• Timing, amount of shortening associated to the propagation of the North Anatolian Fault deduced from mapping and critical revision of the stratigraphy.• Reconstruction of the westward propagation of the NAF in the Dardanelles region. AbstractPropagation processes of plate-scale faults through continental lithosphere are poorly documented. The North Anatolian fault (NAF) is a continental right-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…A second strike-slip system is evidenced at the South Marmara Fault and the Ganos segment, both corresponding to positive flower str uctures for med at a restraining bend (Fig. 2 ; Le Pichon et al 2014 ;Karakas et al 2018 ). These structures record the beginning of the localization of the North Anatolian Shear System in the Pliocene (Armijo et al 1999 ;Le Pichon et al 2014.…”
Section: Tectonic Configuration Of the North Anatolian Fault In The N...mentioning
confidence: 90%
“…A second strike-slip system is evidenced at the South Marmara Fault and the Ganos segment, both corresponding to positive flower str uctures for med at a restraining bend (Fig. 2 ; Le Pichon et al 2014 ;Karakas et al 2018 ). These structures record the beginning of the localization of the North Anatolian Shear System in the Pliocene (Armijo et al 1999 ;Le Pichon et al 2014.…”
Section: Tectonic Configuration Of the North Anatolian Fault In The N...mentioning
confidence: 90%
“…Recently, however, it was claimed that the current strike-slip regime of the entire NAF initiated already in the late Miocene, at an age of 11.4 ± 2.4 Ma, and that east-west propagation may not have taken place (Nuriel et al, 2019). The Pliocene age of NAF initiation in the Dardanelles region is mainly based on the hypothesis that the Formation post-dates the MES (Armijo et al, 1999;Karakas et al, 2018). Here, we have shown that this formation is about 4 Ma older than previously reported, which implies that, if the tectonic reconstructions in the region are correct, the age the NAF initiation in the Dardanelles domain also converges to a late Miocene scenario.…”
Section: Palaeogeographic and Tectonic Implicationsmentioning
confidence: 99%
“…Recently, the debate revived again by the documentation of the MES in the Seddülbahir and sections, supported this time by the presence of the Pliocene nannofossil Ceratolithus acutus in the Fm (Melinte-Dobrinescu et al, 2009). The presence of this nannofossil led to the hypothesis that the deposits correspond to the marine Zanclean flooding (Karakas et al, 2018), when Atlantic waters cascaded into the largely desiccated Mediterranean basin at the end of the Messinian Salinity Crisis (5.33 Ma). It has, however, been shown that C. acutus is not a reliable marker in Mediterranean and Paratethys environments (Di Stefano and Sturiale, 2010;Van Baak et al, 2016aStoica et al, 2018;Golovina et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation